Development and characterization of nanomaterials-based “green electronics” sensors - Zhang, Longyang (Nanyang Technological University, 2024)
This dissertation primarily develops and characterizes a nanomaterial-based "green electronics" electrochemical sensor for detecting codeine. The study utilized Screen Printed Electrodes (SPE) and Cyclic Voltammetry (CV), combined with nanocomposite electrodes of gold nanoparticles and graphene oxide (GO), to optimize the electrode preparation parameters. Through orthogonal experimental design, the study systematically determined the optimal experimental conditions for enhancing electrode performance. This research demonstrates that the electrochemical sensor has high sensitivity and selectivity for codeine, with a detection linear range of 0.118 μM-1.512 μM and a detection limit of 55.6 nM. The research not only provides an effective tool for the rapid and accurate detection of codeine but also offers new possibilities for public health and clinical applications.